Design of an IoT-Based Server Room Temperature Security Monitoring System Using a Microcontroller and Fuzzy Logic Method - Yuma Akbar; Tri Wahyudi; Sugiyono Sugiyono; Ghofurur Nawangsah (Journal of Engineering, Electrical and Informatics, 2022)
PT. Sridatta Prastama Telecommunications (PRASTATEL) as a company in the field of telecommunications service providers must provide non-stop cell phone / VoIP servi-ces. Devices that work 24 hours non-stop by minimizing the damage that occurs, must be supported by monitoring to ensure the system is running properly. If there is a sig-nificant increase in temperature, it can affect system performance or cause damage to the hardware side. The cooler in the server room is felt to be not optimal because the cooler is often constrained by frequent power outages or the cooler turns off and avoids suspicious activities / activities that occur in the server room because the server room administrator is not always on site. From the problems described above, a solution is needed to monitor the system remotely. So that the system is able to know changes in room temperature (Monitoring) in real time and monitor whether there is activity oc-curring in the server room. By using Internet of Things (IoT) technology, the NO-DEMCU ESP-8266 device and the fuzzy logic method which basically maps an input space into an output space that is applied to the server room temperature sensor. This monitoring system uses the Telegram application to receive notifications in the form of text or images. So that it can monitor temperature changes and activities that occur in the server room in real time and accurately. Therefore the server room administrator does not have to be on the site.